FE-MG INTERDIFFUSION IN MAGNESIOWUSTITE UP TO 35 GPA - Yamazaki D.; Irifune T. (My University, 2003)
Fe-Mg interdiffusivities in (Fe,Mg)O magnesiowustite have been measured in experiments conducted at pressures of 7-35 GPa and temperatures of 1573-1973 K using a Kawai-type high-pressure apparatus. The diffusion profiles were measured across the interface between MgO and (Fe0.5,Mg0.5)O samples by electron microprobe analysis, and the Fe-Mg interdiffusivities were determined as DFe-Mg=D0exp{-E*(1+PV*Mg/E*Mg)/RT}, where D0=4.1(+16.1-3.3)x10-7 m2/s, E*=(1-CMg)E*Fe+CMgE*Mg (activation energy for the concentration of Mg, where E*Fe=113(+/-74) kJ/mol and E*Mg=226(+/-32) kJ/mol), the activation volume V*Mg=1.8(+/-1.2)x10-6 m3/mol. By extrapolating these results to the P-T conditions of the core-mantle boundary, we conclude that the interdiffusivity of Fe-Mg in magnesiowustite at the bottom of the lower mantle is at least one order of magnitude larger than that at the top of the lower mantle.
Keywords: MAGNESIOWUSTITE; INTERDIFFUSION; LOWER MANTLE; HIGH-PRESSURE EXPERIMENT